Transformation of the Value-Semantic Sphere of Pathological Players in the Conditions of Rehabilitation - Yurievna, Zinina Anna; Dzakhotovna, Gurieva Svetlana; Uruzbekovna, Gogitsaeva Olga (Journal of Intellectual Disability - Diagnosis and Treatment, 2021)
The spread of gambling addiction is one of the serious problems of modern society. A person involved in gambling creates preconditions for inevitable failure. Effective rehabilitation involves the reconstruction of the personality and aims to return the addict to a healthy and socially valuable life. The value-semantic sphere serves as one of the factors of psychological adaptation and the purpose of psychological correction of game addicts. The present research aimed to study the peculiarities of the transformation of the value-semantic sphere of pathological players in the context of a rehabilitation program. The research involved 42 pathological players undergoing a rehabilitation program for 6 months. We used methods: "Diagnosis of Interpersonal Relationships" by Leary; "Personality Time Perspective Questionnaire" by Zimbardo; "Meaning-Life Orientations" Leontiev; Stolin’s Self-Ratio Questionnaire; "Morphological test of life values" by Sopov and Karpushina and personal data questionnaire. As a result of the study, the connection between the participation in the rehabilitation program and the change of the relationship profile of the pathological players to a more independent one was found. Changes in the time perspective of positive future, an increase of meaningfulness of life, an increase of the level of self-esteem, and a decrease of self-blame were revealed. The change of value from material provision to self-development and acceptance of oneself in the context of rehabilitation was revealed. As a result of the research, it was established that in rehabilitation conditions, the transformation of the value-semantic sphere of pathological players towards more adaptive is possible.